Training decision-makers in flood response with system dynamics. Issue 2 (4th April 2016) - Berariu, Romana; Fikar, Christian; Gronalt, Manfred; Hirsch, Patrick
Abstract : Purpose: – The purpose of this paper is to present a training model for decision makers that covers the complexity which is inherent in decision-making processes in times of floods. Design/methodology/approach: – Through literature review, case study analysis and iterative interviews with decision-makers, the model was established. It enables one to simulate different scenarios depending on selected influencing factors and was implemented with Stella 9.1. Findings: – Flood events are highly complex and their development process is significantly influenced by various conditions. The findings show that the most important factor is the water level which determines the time available to respond. The presented System Dynamics (SD) model has the capability to capture such complex settings. Through what-if analysis and the comparison of different scenarios, learning effects are achieved by using the model. Research limitations/implications: – The level of abstraction is high. Not all influencing variables can be incorporated due to the variety of flood events. Based on experts' recommendations, the most relevant factors were included as areas of focus in the model. Practical implications: – The generated model is presented to facilitate holistic comprehension of the modelling process. It offers the possibility to start learning processes through scenario analyses in order to strengthen decision-makers' understanding of complexity. Originality/value: – To the best of our knowledge, there are no comparable studies that focus on the generation process of building an SD-model for educational purposes in flood response.